Effects of root exudates of woody species on the soil anti-erodibility in the rhizosphere in a karst region, China - Wang, Zhen Hong; Fang, Hong; Chen, Mouhui (PeerJ Preprints, 2016)
Introduction: The rhizospheres, the most active interfaces between plants and soils, play a central role in a long-term maintenance of the biosphere. The anti-erodibility of soils (AES) regulated by the root exudates is crucial to the stability of the rhizospheres. However, scientists still remain unclear regarding the key organic matter in the root exudates to affect the AES and interspecific variation. Methods: We used an incubation of soils to test the effects of the root exudates from 8 woody plant species on a change in soil aggregation, and identified the organic matter in these root exudates with gas chromatograph-mass spectrometer (GC-MS) and biochemical methods. Furthermore, the relationships between the organic matter in the exudates and the AES in the rhizosperes of the 34 additional tree species were analyzed. Results: The water-stable aggregates of the soils incubated with the root exudates increased by 15-50% on average compared with controls, and the interspecific differences were significant. The root exudates included hundreds of specific organic matter, in which hydrocarbon, total sugar, total amino acids and phenolic compounds were crucial to the AES. These types of the matter could explain about 20-75% of the variation in total effects of the root exudates on the AES quantified by aggregate status, degree of aggregation, dispersion ratio and dispersion coefficient. Discussion: Effects of the root exudates on the AES and the interspecific variation are as important as those of root density, litters and vegetation covers. A range of studies have explored the effects of root density, litters, vegetation covers and types on the AES, but little attention has been given to the effects of the root exudates on the AES. Different plants secrete the different relative contents of the organic matter resulting in the variation of the effects of the root exudates on the AES. Our study quantified the causal relationships between the root exudates and the AES from modeling experiments in laboratory to actual effects in the field, and indicated the interspecific variation of the AES and the organic matter in the root exudates. Conclusions: The study recognized more organic compounds in the exudates related to the AES. These results can enhance the understanding of the stability of the soils in a slope and be applied to ecosystem restoration.
Keywords: root exudates; anti-erodibility of soils; soil erosion; woody plants; karst; aggregate status; degree of aggregation; dispersion ratio; rhizosphere; the interspecific differences; gas chromatograph-mass spectrometer; soil incubation; micro-aggregates; water-stable aggregates